2019
DOI: 10.1111/opn.12220
|View full text |Cite
|
Sign up to set email alerts
|

Nursing practice with hospitalised older people: Safety and harm

Abstract: Background Nursing teams work with hospitalised older people in institutions, which prioritise a biomedical model of care. This model does not fit the needs of older people because it emphasises efficacy and a narrow definition of patient safety, but does not prioritise functional needs. Nursing care is provided around the clock within the context of fiscal restraints as well as negative societal and nursing perspectives about ageing and old people. Yet, nursing perceptions of managing safety and potential har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 83 publications
3
29
0
1
Order By: Relevance
“…Dahlke et al () integrative review of nursing practices related to safety revealed that nurses often chemically and/or physically restrain, or limit older healthcare users’ mobility under the guise of keeping them ‘safe’. Moreover, in healthcare institutions where the emphasis is on zero falls, nurses are more likely to either restrain or limit the mobility of healthcare users (Dahlke et al, ).…”
Section: Nurses’ Perceptions Of Healthcare Usersmentioning
confidence: 99%
See 4 more Smart Citations
“…Dahlke et al () integrative review of nursing practices related to safety revealed that nurses often chemically and/or physically restrain, or limit older healthcare users’ mobility under the guise of keeping them ‘safe’. Moreover, in healthcare institutions where the emphasis is on zero falls, nurses are more likely to either restrain or limit the mobility of healthcare users (Dahlke et al, ).…”
Section: Nurses’ Perceptions Of Healthcare Usersmentioning
confidence: 99%
“…Dahlke et al () integrative review of nursing practices related to safety revealed that nurses often chemically and/or physically restrain, or limit older healthcare users’ mobility under the guise of keeping them ‘safe’. Moreover, in healthcare institutions where the emphasis is on zero falls, nurses are more likely to either restrain or limit the mobility of healthcare users (Dahlke et al, ). One explanation for these nursing practices might be that nurses are protecting their position as a subordinate within the healthcare institution and thus treating the healthcare user as an object to be manipulated in order to avoid the negative consequences of a fall, which would be seen ‘unsafe’.…”
Section: Nurses’ Perceptions Of Healthcare Usersmentioning
confidence: 99%
See 3 more Smart Citations